1997
DOI: 10.1073/pnas.94.6.2528
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of experimental allergic encephalomyelitis by targeting nitric oxide and peroxynitrite: Implications for the treatment of multiple sclerosis

Abstract: In this study we provide further evidence associating activated cells of the monocyte lineage with the lesions of multiple sclerosis (MS). Using a combination of immunohistochemistry and reverse transcriptase-dependent in situ polymerase chain reaction analysis, we have identified monocytes expressing inducible nitric oxide synthase (iNOS) to be prevalent in the plaque areas of post mortem brain tissue from patients with MS. In addition, we have obtained evidence of the nitration of tyrosine residues in brain … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

14
206
5

Year Published

1999
1999
2005
2005

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 305 publications
(225 citation statements)
references
References 27 publications
14
206
5
Order By: Relevance
“…For example, ascorbic acid, another biologically relevant antioxidant, was ϳ15-fold less effective at inhibiting DHR 123 oxidation mediated by ONOO Ϫ elaborated by activated macrophages. More important in the context of nitrotyrosine formation in MS and EAE (1)(2)(3)(4)(5), UA efficiently inhibits ONOO Ϫ -mediated tyrosine nitration in the presence and absence of a source of carbonyl anion. Apart from inactivating ONOO Ϫ , UA does not appear to have any significant effect on in vitro measures of immune and inflammatory cell function relevant to EAE.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…For example, ascorbic acid, another biologically relevant antioxidant, was ϳ15-fold less effective at inhibiting DHR 123 oxidation mediated by ONOO Ϫ elaborated by activated macrophages. More important in the context of nitrotyrosine formation in MS and EAE (1)(2)(3)(4)(5), UA efficiently inhibits ONOO Ϫ -mediated tyrosine nitration in the presence and absence of a source of carbonyl anion. Apart from inactivating ONOO Ϫ , UA does not appear to have any significant effect on in vitro measures of immune and inflammatory cell function relevant to EAE.…”
Section: Discussionmentioning
confidence: 99%
“…Our approach to examining the contribution of ONOO Ϫ to the pathogenesis of EAE has been to determine whether reagents that interfere with its chemical reactions also inhibit the development or progression of the disease (1,5,15). Table I summarizes the results of a survey of a variety of compounds that have been assessed for the capacity to inhibit oxidation of DHR 123 by ONOO Ϫ produced either chemically by SIN-1 or biologically by LPS-stimulated RAW monocytes.…”
Section: Capacity Of Ua To Inhibit Onoo ϫ Reactivity In Vitromentioning
confidence: 99%
See 2 more Smart Citations
“…It was proposed that the mechanism of EAE inhibition in iron-deficient mice involves the delivery and metabolism of iron for optimal CD4 þ T-cell development (Grant et al, 2003). Some investigators have shown iNOS inhibition as well as NO scavenging to suppress EAE (Cross et al, 1994;Zhao et al, 1996;Hooper et al, 1997;Jolivalt et al, 2003), whereas others have shown iNOS inhibition (O'Brien et al, 1999(O'Brien et al, , 2001 or NO donor (Xu et al, 2001) to aggravate or ameliorate EAE, thus not clarifying the exact role for NO .…”
Section: Oxidative Stress and Antioxidantsmentioning
confidence: 99%